Facile template-free synthesis of the CuO microflowers with enhanced photocatalytic properties. (10th November 2017) - Ahmadi, Marzieh; Padervand, Mohsen; Vosoughi, Manouchehr; Roosta Azad, Reza
Abstract: CuO flower-like microcrystals, prepared by a facile template-free thermal method, showed incredible photocatalytic activity towards degradation of Acid Blue 92 (AB92), an organic wastewater, Escherichia coli and Staphylococcus aureus pathogenic bacteria under visible light. The products were well characterised by X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET), scanning electron microscope (SEM), Fourier transform infrared (FTIR), photoluminescence spectroscopy (PL) and diffuse reflectance spectra (DRS) analysis methods. The XRD pattern of the products well confirmed the formation of copper oxide crystalline phase without any other impurities. The results of the photocatalytic experiments exhibited that the products were efficiently able to degrade the dye compound and pathogenic bacteria in the aqueous phase under both visible light and natural solar energy. Furthermore, according to the results from recycling experiments, the removal efficiency was smoothly dropped to 78% after four times of repeated using.